2010
DOI: 10.1124/mol.109.063172
|View full text |Cite
|
Sign up to set email alerts
|

Copper Transporters and the Cellular Pharmacology of the Platinum-Containing Cancer Drugs

Abstract: Multiple lines of evidence indicate that the platinum-containing cancer drugs enter cells, are distributed to various subcellular compartments, and are exported from cells via transporters that evolved to manage copper homeostasis. The cytotoxicity of the platinum drugs is directly related to how much drug enters the cell, and almost all cells that have acquired resistance to the platinum drugs exhibit reduced drug accumulation. The major copper influx transporter, copper transporter 1 (CTR1), has now been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
244
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(253 citation statements)
references
References 74 publications
5
244
1
3
Order By: Relevance
“…Ctr1 controls copper uptake, while ATP7A and ATP7B control the copper export from cells (23)(24)(25). Previous studies have identified that copper ion transport proteins are closely associated with the development of cisplatin resistance (16,26,27). These copper transporters include Ctr1 and ATP7B and ATP7A (23,28), which together regulate the overall intracellular cisplatin levels.…”
Section: A B Cmentioning
confidence: 99%
“…Ctr1 controls copper uptake, while ATP7A and ATP7B control the copper export from cells (23)(24)(25). Previous studies have identified that copper ion transport proteins are closely associated with the development of cisplatin resistance (16,26,27). These copper transporters include Ctr1 and ATP7B and ATP7A (23,28), which together regulate the overall intracellular cisplatin levels.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, much work has centred on the importance of copper transporters, such as CTR1, which can mediate uptake of cisplatin by yeast [4,5]. Although some evidence suggests that in human cells CTR1 can take up cisplatin and deliver it in a form that is capable of binding DNA and triggering apoptosis [6], iconoclastic data continue to emerge [7]. Other membrane proteins may also play a role in the uptake of platinum drugs and, in collaboration with the Giacomini laboratory, we showed that cells overexpressing the organic cation transporters OCT1 and OCT2 were significantly more sensitive to oxaliplatin than cisplatin [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to play a major role in CisPt uptake and cytotoxicity [3]. The absence of Ctr1 render cells resistant to CisPt [4] whereas patients with high levels of Ctr1 in their tumors responded better to platinum drug treatment [5].…”
Section: Introductionmentioning
confidence: 99%